The Influence of SIAM, Data Efficiency and Accuracy, Audit Transparency, and Management Accountability on Smart Governance with Good Governance as a Mediating Variable - Amin, Rofikul; Kurniawan, Setia Budi; Suprayitno, Adi (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of the digitalization of the Management Administration Information System (SIAM), data efficiency and accuracy, transparency and audit trail, and managerial accountability on smart governance with good governance as a mediating variable. A quantitative approach was used with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method involving 110 respondents from government agencies. The results of the analysis indicate that the digitalization of SIAM has a significant effect on data efficiency and accuracy, which in turn increases transparency and managerial accountability. Each variable has a significant contribution to good governance, which then strongly mediates the relationship towards smart governance. The R-square value indicates that the model has adequate predictive power, and the f-square test and path coefficient indicate a substantial strength of the relationship. This study confirms that the success of smart governance is not only determined by technological aspects, but also heavily depends on transparent, accountable, and efficient governance.